THE USE OF CODE-SWITCHING IN ONLINE SOCIAL MEDIA (LINE) BY SENIOR-HIGH-SCHOOL ALUMNI IN SOUTH SUMATRA - Septiani, Merta; Petrus, Ismail; Yunus, Muhammad (University of Sriwijaya, 2018)
Abstract: Code-switching is an important issue in bilingual education. Many researchers have investigated its value in classroom teaching and learning process. However, this paper focuses on code-switching of English and Indonesian which happens in online social media. This paper identifies the types, topics, and factors motivating code switching in the online chatroom (LINE) among 80 bilingual young adults, the alumni of a senior high school in South Sumatra. Cross-sectional survey design was used in this study. The data were collected through documenting, questionnaire, and interview. Later, the data were analyzed by using descriptive and inferential statistics. The findings of the study revealed that the senior-high-school alumni mostly used intra-sentential code-switching (67%). The topics in the chatroom included social issues, technology, education, politics, health, economics, and faith; the reasons why they used code-switching were avoiding misunderstanding (75%), being easier to speak in one?s own language (52.5%), not knowing the English words (28.7%), no similar words in L1/L2 (27.5%), filling the stopgap (25%), giving emphasis (25%), conveying intimacy (18.8%), and having privacy (18.8%). In addition, the statistics showed that the topics and factors had a significant relationship. Code switching can be a useful strategy in online interaction to serve many purposes.Keywords: code switching, bilingual, social media